Time, Space and Affection: arts education with children with high capacity and motivation towards learning - Maldonado-Esteras, Stella (Arte, Individuo y Sociedad, 2026)
There is much talk about the educational shift, about the urgent need to transform teaching and learning processes. Here, in this article, under the umbrella of pedagogical approaches such as affective and committed education, in parallel with experimental action, a project aimed at highly motivated and highly capable children is presented which, beyond labels, seeks to highlight the power of the arts as a vehicle for arts education to build learning communities based on affection, free creativity, reflection, dialogue, and multidimensional communication. In this community, shared space and time played a very important role in exploring possibilities of being and existing, shaping personal and collective identities, imagining and creating possible worlds, and critically analyzing the reality in which we live.Some conclusions have been drawn about what this community was and meant through texts, images, and opinions of the protagonists themselves, making use of ethnography which, due to its qualitative nuances, is closer to a personal ideology of action and research.
Keywords: Arts education; affection; arts; high abilities; motivation